A report of Bilharziella polonica cercariae in Knowsley Safari, Prescot, United Kingdom, with notes on other trematodes implicated in human cercarial dermatitis. (28th October 2022) - Juhász, A.; Barlow, S.E.J.; Williams, H.; Johnson, B.; Walsh, N. Davies; Cunningham, L. C.; Jones, S.; LaCourse, E. J.; Stothard, J. R.
Abstract: As part of surveillance of snail-borne trematodiasis in Knowsley Safari (KS), Prescot, United Kingdom, a collection was made in July 2021 of various planorbid ( n = 173) and lymnaeid ( n = 218) snails. These were taken from 15 purposely selected freshwater habitats. In the laboratory emergent trematode cercariae, often from single snails, were identified by morphology with a sub-set, of those most accessible, later characterized by cytochrome oxidase subunit 1 ( cox 1) DNA barcoding. Two schistosomatid cercariae were of special note in the context of human cercarial dermatitis (HCD), Bilharziella polonica emergent from Planorbarius corneus and Trichobilharzia spp. emergent from Ampullacaena balthica . The former schistosomatid was last reported in the United Kingdom over 50 years ago. From cox 1 analyses, the latter likely consisted of two taxa, Trichobilharzia anseri, a first report in the United Kingdom, and a hitherto unnamed genetic lineage having some affiliation with Trichobilharzia longicauda . The chronobiology of emergent cercariae from P. corneus was assessed, with the vertical swimming rate of B. polonica measured. We provide a brief risk appraisal of HCD for public activities typically undertaken within KS educational and recreational programmes.